2017
DOI: 10.1039/c6ra26386k
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical one pot synthesis of novel spiroacridines catalyzed by magnetically functionalized Fe3O4nanoparticles with chitosan as a reusable effective catalyst

Abstract: Fe3O4@CS–SO3H NPs low toxicity, easy preparation, recyclable catalyst for the synthesis of spiroacridine in aqueous ethanol is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The catalytic strength of our specific catalyst (biochar/Fe 3 O 4 /PVIm/Ag) is compared with the recently detailed MCRs including acenaphthoquinone, malononitrile, and dimethyl ketone to use 2′-amino-tetrahydro-2 H -spiro[acenaphthylen-1,4′-chromeno]-3′-carbonitrile ( 14a ) and different catalysts, such as CaCl 2 57 , Fe 3 O 4 @Cs-CsO 3 H 56 , Na 2 EDTA 58 , HAuCl 4 . 3H 2 O 59 , Meglumine 41 , Fe 2 O 3 60 , HEAA 61 , Cu(OAc) 2 .H 2 O 46 , Fe 3 O 4 @CS-SO 3 H NPs 62 , Amb-400Cl (IRA-400 Cl) 63 , C 4 (DABCO-SO 3 H) 2 .4Cl 64 , Carbon-SO 3 H 65 , 1-butyl-3-methylimidazolium hydroxide ([bmim][OH] 66 , DBU 67 , (SB-DBU)Cl 68 , PEG-Ni nanoparticles 69 , trisodium citrate dihydrate 70 , PC/AgNPs 35 and new catalyst biochar/Fe 3 O 4 /PVIm/Ag. It seems that our new catalyst is better than other catalysts in more items.…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic strength of our specific catalyst (biochar/Fe 3 O 4 /PVIm/Ag) is compared with the recently detailed MCRs including acenaphthoquinone, malononitrile, and dimethyl ketone to use 2′-amino-tetrahydro-2 H -spiro[acenaphthylen-1,4′-chromeno]-3′-carbonitrile ( 14a ) and different catalysts, such as CaCl 2 57 , Fe 3 O 4 @Cs-CsO 3 H 56 , Na 2 EDTA 58 , HAuCl 4 . 3H 2 O 59 , Meglumine 41 , Fe 2 O 3 60 , HEAA 61 , Cu(OAc) 2 .H 2 O 46 , Fe 3 O 4 @CS-SO 3 H NPs 62 , Amb-400Cl (IRA-400 Cl) 63 , C 4 (DABCO-SO 3 H) 2 .4Cl 64 , Carbon-SO 3 H 65 , 1-butyl-3-methylimidazolium hydroxide ([bmim][OH] 66 , DBU 67 , (SB-DBU)Cl 68 , PEG-Ni nanoparticles 69 , trisodium citrate dihydrate 70 , PC/AgNPs 35 and new catalyst biochar/Fe 3 O 4 /PVIm/Ag. It seems that our new catalyst is better than other catalysts in more items.…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic potency of our novel catalyst (PC/AgNPs) was compared with the same recently reported MCR, involving acenaphthenequinone, malononitrile and dimedone for the preparation of 2′-amino-tetrahydro-2 H -spiro[acenaphthylene-1,4′-chromene]-3′-carbonitrile ( 12b ) with various catalysts such as CaCl 2 , 164 Fe 3 O 4@ Cs-SO 3 H, 163 Na 2 EDTA, 165 HAuCl 4 .3H 2 O, 166 Meglumine, 135 Fe 2 O 3, 167 HEAA, 168 Cu(OAc) 2 . H 2 O, 169 Amb-400Cl (IRA-400 Cl), 170 Fe 3 O 4 @CS-SO 3 H NPs, 171 C 4 (DABCO-SO 3 H) 2 . 4Cl, 172 1-butyl-3-methylimidazolium hydroxide ([bmim][OH], 173 Carbon–SO 3 H, 174 DBU, 175 (SB-DBU)Cl, 176 PEG-Ni nanoparticle-catalyzed, 177 trisodiumcitrate dehydrate, 178 with that of PC/AgNPs novel catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Moshkin et al 24 reported the reaction of non-stabilized azomethine ylide 58, generated in situ from sarcosine (2), formaldehyde (57), with 1 to give 5-aryloxazolidine 59. Subsequent acid-mediated hydrolysis of the oxazolidine gave aminoalcohol 60 in 47% yield (Scheme 18).…”
Section: Scheme 17 Synthesis Of Piperazinyl-quinolinyl Dispiroheterocmentioning
confidence: 99%
“…Next, treatment of the Fe 3 O 4 @CS NPs with chlorosulfonic acid led to formation of the corresponding catalyst. 57 In 2011, Bazgir et al reported a one-pot synthesis of spiro[acenaphthylene-indenopyridine] derivatives 117-120 in high yields (75-89%) by the condensation reactions of 1, indane-1,3-dione (112), and various enamines 121-123 under refluxing conditions. [58][59][60] This group also used Lproline as an organocatalyst in a similar reaction for the synthesis of spirocycles 120 in 79-84% yields (Scheme 43).…”
Section: Scheme 41 Synthesis Of Spiroacridine Derivatives 115mentioning
confidence: 99%